The Thirteen Pragmatisms and Other Essays - Lovejoy, Arthur O. (Johns Hopkins University Press, 2019)
Originally published in 1963. The essays in this volume are critical and, with one exception, directed against the philosophic movement of pragmatism. "The Thirteen Pragmatisms" is an exercise in logical analysis and is a challenge to a group of philosophers who have taken on a collective name to show how their apparent diversities are to be reconciled. Few philosophers would call themselves orthodox followers of this train of thought, so these essays can be studied without a sense of personal injury that deadens the critical faculty and obscures insight. In The Thirteen Pragmatisms and Other Essays, logical technique is on display: the author's keenness in spotting double meanings and his ability to rephrase them in univalent form. This collection of essays should afford students of philosophy a set of cases in which they need not take sides but which give them an analytical method they can practice themselves on contemporary issues. The fact that these essays are on the whole critical gives them a heuristic value that dogmatic or expository essays would not have.